CT Angiography or Cardiac MRI for Detection of Coronary Artery Aneurysms in Kawasaki Disease - van Stijn, Diana; Planken, Nils; Kuipers, Irene; Kuijpers, Taco (Frontiers in Pediatrics, 2021)
Background— Kawasaki disease (KD) is an acute vasculitis that mainly affects the coronary arteries. This inflammation can cause coronary artery aneurysms (CAAs). Cardiac assessment consists of risk stratification for the development of myocardial ischemia, based on Z score (luminal diameter of the coronary artery corrected for body surface area). Echocardiography is the primary imaging modality in KD but has several important limitations. Coronary computed tomographic angiography (cCTA) and Cardiac MRI (CMR) are non-invasive imaging modalities and of additional value for assessment of CAAs with a higher diagnostic yield compared to echocardiography. The objective of this single center study is to determine the difference of coronary artery assessment of cCTA versus CMR children with KD. Methods and results— Out of 965 KD patients from our database, a total of 111 cCTAs (104 patients) and 311 CMR (225 patients) have been performed since 2010. For comparison we identified 54 KD patients who had undergone both cCTA and CMR. CMR missed 50% of the CAAs identified by cCTA and thereby only identified 8 patients with CAAs compared to 14 patients by cCTA. Conclusions— Our single center study in KD demonstrates that cCTA is the better modality to detect CAAs as it is capable to detect more CAAs than CMR.